Osmolar-gap in the setting of metformin-associated lactic acidosis - Mohamed Nabil Elshafei (9960500) (2020)
Rationale Metformin-associated lactic acidosis (MALA) is a rare adverse effect that has significant morbidity and mortality. MALA is a high anion gap (AG), nonosmolar acidosis. Associated osmolar-gap (OG) is rarely reported, so finding an OG may make the diagnosis of MALA challenging. Patient concerns Forty-five years’ old type II diabetic patient on metformin presented to emergency with a two-day history of vomiting, watery diarrhea, and mild abdominal discomfort. On examinations, he looked dehydrated. Investigation revealed acute kidney injury (AKI) with a high lactic acid (LA) level of 24 mmol/L, pH of 6.8, AG of 40, and an OG of 20 mOsm/kg Diagnoses The presence of an OG made the diagnosis challenging; the history was negative for alcohol, osmolar substance, or illicit drug ingestion or use. The toxicology screen was negative. After ruling out plausible causes of AG and OG, MALA was deemed the likely reason for his presentation likely precipitated by dehydration and AKI. Interventions He underwent two sessions of hemodialysis, afterward managed with fluid hydration. Outcomes On day 3, he was in the polyuric phase suggestive of acute tubular necrosis. His serum creatinine improved afterward with improved acidosis; after 8 days, he was discharged in stable condition. Lessons MALA is a rare side effect of metformin therapy. Acute kidney injury is a known precipitant of MALA. In our review, we highlight the association of MALA and the presence of an OG. We believe that treating physicians should be aware of this relationship to avoid delaying or overlooking such an important diagnosis. Other Information Published in: Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/md.0000000000022492